ON INCREASING THE EFFICIENCY OF A DISCRETE ORDINATES RADIATIVE TRANSFER METHOD WITH PERIODIC RELATIONS - de Abreu, M. P. (Revista de Engenharia Térmica, 2005)
In this article, improvements in a recently developed discrete ordinates method the two-component method - are reported. The method solves conservative and non-conservative radiative heat transfer problems with anisotropic scattering on a multislab domain irradiated from one side with a radiation beam. The beam here consists of a monodirectional (singular) stream and of a continuous (regular) distribution in angle. Specifically, the computational efficiency of this two-component method has been increased with the help of new periodic relations for the coupling coefficients that appear in the numerical component of the method. With these periodic relations, memory usage requirement for storing the (usually large number of) coupling coefficients has been halved, while saving computer time from unnecessary computation of redundant coefficients. The increased efficiency of the two-component method has been illustrated with numerical results and discussion of a model problem in shortwave radiative transfer.